2005
DOI: 10.1119/1.1862636
|View full text |Cite
|
Sign up to set email alerts
|

Relation between students’ problem-solving performance and representational format

Abstract: An analysis is presented of data on students' problem-solving performance on similar problems posed in diverse representations. Five years of classroom data on 400 students collected in a second-semester algebra-based general physics course are presented. Two very similar Newton's third-law questions, one posed in a verbal representation and one in a diagrammatic representation using vector diagrams, were given to students at the beginning of the course. The proportion of correct responses on the verbal questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
1
15

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 68 publications
(24 reference statements)
8
135
1
15
Order By: Relevance
“…Previous studies concerned with multiple representations [26,32] have evoked the key importance of students' fluency with different kinds of representations and in translating information among them. In the context of chemistry, Kozma [44] reported that when novice students are presented with multiple depictions, they attended to these representations on an individual basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies concerned with multiple representations [26,32] have evoked the key importance of students' fluency with different kinds of representations and in translating information among them. In the context of chemistry, Kozma [44] reported that when novice students are presented with multiple depictions, they attended to these representations on an individual basis.…”
Section: Discussionmentioning
confidence: 99%
“…Students' difficulties in handling particular representations such as diagrammatic and graphical representation in specific topics were investigated [21][22][23][24][25]. Studies were also geared towards exploring problem solving performance and hence differences in strategies with a change in representation [26][27][28]. The application of multiple representations for conceptual understanding [29,30] and enhancing problem solving performance [31,32] was additionally explored.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Meltzer [10] notes that "the instructor's view of the ease or difficulty of a particular representation in a particular context might not match the views of a large proportion of students" (p. 473). This inability of physics teachers to judge the difficulties that a given representation may pose for students has also been reported by other researchers [15,48,49].…”
Section: B the Appreciation Of Disciplinary Affordances Of Representmentioning
confidence: 99%
“…This theoretical article is about the teaching and learning challenges that arise from students experiencing this partiality of representations, where important physics aspects are not initially discernible. These issues are educationally important because what creates a powerful communicative system for physics at the same time manifests in the difficulties students experience in terms of becoming "fluent" [2] (p. 28) in the disciplinary-specific representations [2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Theoretical details from the literature, together with the concept of disciplinary affordance [11,12], are used to underpin a case that physics representations need to be "unpacked" for students.…”
Section: Introductionmentioning
confidence: 99%
“…These interventions use multiple contexts to augment graphical skill. Differences in the representation of physics problems were found to produce strong differences in performance [21][22][23]. Differences in performance based on representation were also influenced by the context of the problems [22,23].…”
Section: Introductionmentioning
confidence: 99%